IGF1 Promotes Adipogenesis by a Lineage Bias of Endogenous Adipose Stem/Progenitor Cells. (27th May 2015) - Hu, Li; Yang, Guodong; Hägg, Daniel; Sun, Guoming; Ahn, Jeffrey M.; Jiang, Nan; Ricupero, Christopher L.; Wu, June; Rodhe, Christine Hsu; Ascherman, Jeffrey A.; Chen, Lili; Mao, Jeremy J.
Abstract Adipogenesis is essential for soft tissue reconstruction following trauma or tumor resection. We demonstrate that CD31−/34+/146− cells, a subpopulation of the stromal vascular fraction (SVF) of human adipose tissue, were robustly adipogenic. Insulin growth factor‐1 (IGF1) promoted a lineage bias towards CD31−/34+/146− cells at the expense of CD31−/34+/146+ cells. IGF1 was microencapsulated in poly(lactic‐co‐glycolic acid) scaffolds and implanted in the inguinal fat pad of C57Bl6 mice. Control‐released IGF1 induced remarkable adipogenesis in vivo by recruiting endogenous cells. In comparison with the CD31−/34+/146+ cells, CD31−/34+/146− cells had a weaker Wnt/β‐catenin signal. IGF1 attenuated Wnt/β‐catenin signaling by activating Axin2/PPARγ pathways in SVF cells, suggesting IGF1 promotes CD31−/34+/146− bias through tuning Wnt signal. PPARγ response element (PPRE) in Axin2 promoter was crucial for Axin2 upregulation, suggesting that PPARγ transcriptionally activates Axin2. Together, these findings illustrate an Axin2/PPARγ axis in adipogenesis that is particularly attributable to a lineage bias towards CD31−/34+/146− cells, with implications in adipose regeneration. Stem Cells2015;33:2483–2495